THE INFLUENCE OF PRICES, PROMOTIONS AND SECURITY ON SHOPEE ONLINE STORE PURCHASING DECISIONS (Case Study of Management Students at Universitas Malikussaleh) - Sabitah Fina; Khairina AR; Heriyana; Siti Maimunah (RADJA PUBLIKA, 2024)
Current technological developments support e-commerce or business activities through electronic media. Shopee is an online marketplace for buying and selling online easily and quickly. Shopee offers a variety of products ranging from fashion to daily necessities. This research was conducted to determine the influence of price, promotion and security on online shopee purchasing decisions at Malikussaleh University. The population in this study was men and women. Meanwhile, the number of samples used in this research was 93 respondents. This research uses a quantitative type with a sampling technique in the form of purposive sampling which is then carried out by distributing questionnaires to respondents who shop at the Shopee online store. The data analysis method used is multiple linear regression analysis using SPSS 25 and also hypothesis testing. Data analysis uses the classical assumption test, partial test (t), simultaneous test (f) and coefficient of determination test. The results of the research show that: (1) Price has a significant effect on online Shopee purchasing decisions for Malikussaleh University Management students (2) Promotion has no significant effect on Shopee online purchasing decisions for Malikussaleh University Management students (3) Security has a significant effect on Shopee online purchasing decisions for Malikussaleh University Management students. Malikussaleh University Management students and (4) Price, promotion and security have a significant influence on online shopee purchasing decisions among Malikussaleh University Management students.